2017
DOI: 10.1007/s10549-017-4561-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported factors associated with adherence to adjuvant endocrine therapy after breast cancer: an integrative review

Abstract: An increasing number of studies have focused on identifying the patient-reported factors that influence AET adherence and persistence. This review highlights important personal, social, and structural factors that act as facilitators and barriers in adhering to and persisting with long-term AET. Acknowledging and addressing these factors is key to providing women with the care needed to improve suboptimal adherence and persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 71 publications
4
139
2
1
Order By: Relevance
“…Despite the known efficacy of ET, up to 30% of patients with invasive HR+ breast cancer who are prescribed ET never initiate therapy [9]. In addition, 18% to 73% of patients who initiate ET do not complete the prescribed course of treatment [2,4,6,[9][10][11][12][13][14][15][16][17][18][19]. Early discontinuation of therapy is associated with increased recurrence and breast cancer-specific mortality rates, as well as higher medical costs [2,9,11,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the known efficacy of ET, up to 30% of patients with invasive HR+ breast cancer who are prescribed ET never initiate therapy [9]. In addition, 18% to 73% of patients who initiate ET do not complete the prescribed course of treatment [2,4,6,[9][10][11][12][13][14][15][16][17][18][19]. Early discontinuation of therapy is associated with increased recurrence and breast cancer-specific mortality rates, as well as higher medical costs [2,9,11,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous qualitative studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] have furthered our understanding of the subjective experience of AET. An integrative review of the findings from these studies indicates that non-adherence to AET is multifaceted and influenced by several psychosocial factors, such as the experience of side effects, negative attitudes towards AET or medication in general, lack of a routine, and unsatisfactory relationships with healthcare professionals [ 30 ]. This review highlights how some of the factors influencing non-adherence to AET (e.g., side effects, patient-provider communication) are similar to those for non-adherence to medications prescribed for other chronic conditions [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that self-efficacy and social support have a positive effect on drug adherence [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. Self-efficacy, the belief in one's ability or confidence to successfully perform a task or behavior (i.e., taking their medication as prescribed, when traveling, not feeling well or experiencing side effects) [ 32 ], has been shown to influence adherence to EHT, with lower levels of perceived self-efficacy associated with decreased rates of adherence, while higher levels of perceived self-efficacy are associated with higher adherence rates [ [23] , [24] , [25] , [26] ]. Social support from friends and family is also an important determinant of ongoing EHT adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Social support from friends and family is also an important determinant of ongoing EHT adherence. Women who have higher levels of social support had greater adherence compared with women with lower levels of social support from family and friends [ 24 , [27] , [28] , [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%